A solid waste-based geopolymer engineering material for alkali residue treatment and comprehensive utilization

By adding fly ash, iron tailings and desulfurization gypsum to the alkali slag and adding specific additives to form geological polymer engineering materials of solid waste base, the problems of reduced bearing capacity and limited cementation in the engineering soil are solved, and better compactness and mechanical properties are achieved.

CN118026630BActive Publication Date: 2025-03-21NANJING GUOHUAN TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410171899.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-07-28
Filing Date
2024-02-07
Publication Date
2025-03-21
Estimated Expiration
2044-02-07

AI Technical Summary

Technical Problem

In the prior art, alkali slag is prone to pores due to the dissolution and loss of the salts contained in it when serving as engineering soil, resulting in a decrease in bearing capacity, making it difficult to fully meet the mechanical performance indicators of engineering soil. At the same time, the cementing effect of the alkali slag itself is limited and it is difficult to use as a roadbed material.

Method used

By adding fly ash, iron tailings and desulfurization gypsum on the basis of alkali slag, and adding additives such as cement, alkaline exciters, premature strength agents, gel additives and quick-setting agents, solid waste base geological polymer engineering materials are formed. After adding water, the material stimulates the sufficient reaction of the gelled material through the pozzolanic reaction and alkali, producing gel products, blocking pores and improving cementation.

Benefits of technology

The good compactness and strong cementation of the solid waste base geological polymer engineering materials are achieved, which can better meet the mechanical performance indicators of the engineering soil and are suitable for engineering soil in the road base and yard cushion layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004701163400000071
    Figure BDA0004701163400000071
  • Figure BDA0004701163400000081
    Figure BDA0004701163400000081
  • Figure BDA0004701163400000101
    Figure BDA0004701163400000101
Patent Text Reader

Abstract

The present application relates to the technical field of industrial waste residue treatment, and specifically discloses a solid waste-based geopolymer engineering material for alkaline residue treatment and comprehensive utilization and a construction method thereof. The geopolymer engineering material comprises the following components in parts by weight: 56-64 parts of alkaline residue, 18-22 parts of fly ash, 30-50 parts of iron tailings, 10-15 parts of desulfurized gypsum, and 1-5 parts of additives, wherein the components of the additives include cement, alkaline activator, early strength agent, gelling agent, and quick-setting agent. After the mixture formed by adding water to the geopolymer engineering material of the present application is used as engineering soil for the yard cushion layer and the road base layer, it not only exhibits good compaction performance, but also has strong bonding between the particles, which can better meet the mechanical performance indicators of the engineering soil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of industrial waste residue treatment, and more specifically, to a solid waste-based geopolymer engineering material for alkaline residue treatment and comprehensive utilization. Background Art

[0002] Solid waste refers to solid and semi-solid waste materials generated by humans in production, consumption, life and other activities, referred to as solid waste. Taking alkali slag as an example, alkali slag refers to alkaline solid waste discharged in the process of producing soda ash by the ammonia-alkali method. According to statistics, for every ton of soda ash produced, 0.3-0.6 tons of alkali slag will be produced. In addition to alkali slag, fly ash, iron tailings, and desulfurization gypsum are also solid wastes with large annual output. In addition to occupying a large amount of land for stacking, these solid wastes may also cause environmental pollution. In order to reduce the impact of solid waste accumulation, the current mainstream treatment method is to apply solid waste to various construction projects to make high-value utilization of solid waste.

[0003] Calcium carbonate and calcium sulfate mainly contained in the alkali residue can be used as components of the engineering soil skeleton. Therefore, in the related art, some people have tried to use the alkali residue as engineering soil and mix it with water, and use the obtained mixture to build building foundations, road foundations, or to fill low-lying ground.

[0004] Regarding the above-mentioned related technologies, the inventors believe that although the related technologies have realized the utilization of solid waste, the types of solid waste utilized by the technologies are limited, and there is only one type of solid waste, namely, alkali slag. The structure of alkali slag is loose and the maximum dry density is small. When it is used as engineering soil, it is easy to produce pores due to the dissolution and loss of the salts contained in it. The generation of pores will lead to a decrease in bearing capacity. Therefore, alkali slag used alone is often difficult to fully meet the mechanical performance indicators of engineering soil. Moreover, alkali slag is a lightweight backfill material and a high liquid limit soil. It is not easy to lose water. Its own cementation effect is limited, and it is difficult to use it as a roadbed material. Summary of the invention

[0005] The related art only realizes the recycling of alkali residue. When alkali residue is used as engineering soil, it is easy to produce pores due to the dissolution and loss of salts contained in it, resulting in a decrease in bearing capacity, which makes it difficult to fully meet the mechanical performance indicators of engineering soil. Moreover, the cementation effect of alkali residue itself is limited, making it difficult to use as a roadbed material. In order to improve these defects, the present application provides a solid waste-based geopolymer engineering material for alkali residue treatment and comprehensive utilization.

[0006] In the first aspect, the present application provides a solid waste-based geopolymer engineering material for alkaline residue treatment and comprehensive utilization, which adopts the following technical solution:

[0007] A solid waste-based geopolymer engineering material for alkali slag treatment and comprehensive utilization, the geopolymer engineering material comprising the following components in parts by weight: 56-64 parts of alkali slag, 18-22 parts of fly ash, 30-50 parts of iron tailings, 10-15 parts of desulfurized gypsum, and 1-5 parts of additives, wherein the additives comprise cement, an alkaline activator, an early strength agent, a gelling agent, and an accelerating setting agent.

[0008] By adopting the above technical scheme, the present application adds fly ash, iron tailings and desulfurized gypsum on the basis of alkali slag, expands the types of solid wastes used, and adds additives on the basis of solid wastes to obtain solid waste-based geopolymer engineering materials. After the geopolymer engineering material is mixed with water, the activity of the fly ash is stimulated by the alkaline activator and calcium sulfate, and a volcanic ash reaction occurs to produce a certain amount of gel product. The components such as calcium carbonate and calcium sulfate in the alkali slag serve as a skeleton structure and are combined with the gel product. In this process, the alkaline environment provided by the desulfurized gypsum, fly ash and alkaline activator is conducive to the full reaction of the alkali-activated gelling material. The iron tailings provide physical filling inside the alkali slag skeleton, and the active silica therein generates silicate gelling material components under alkaline conditions. The formation of the gel product can block the pores caused by the loss of salts, realize the solidification of soluble salts, and improve the cementation between solid waste particles. When the mixture formed by adding water to the geopolymer engineering material of the present application is used as engineering soil for road base and yard cushion, it not only exhibits good compaction performance, but also has strong bonding between particles, which can better meet the mechanical performance indicators of engineering soil.

[0009] Preferably, the free calcium oxide content of the fly ash is 1-4%.

[0010] By adopting the above technical solution, although fly ash has been widely used in concrete, the free calcium oxide content of fly ash used to produce concrete usually needs to be as low as possible (usually preferably below 1%) to reduce the impact of free calcium oxide on stability. As for the geopolymer engineering material of the present application, due to the existence of the phenomenon that pores are generated by the dissolution and loss of salts, the expansion effect of free calcium oxide has less impact on stability, and can better fill the pores generated by the loss of salts. At the same time, fly ash with a higher free calcium oxide content produces more calcium hydroxide after mixing with water, so it has better gelling properties. Therefore, the present application prefers fly ash with a relatively high free calcium oxide content, which helps to improve the strength performance of the mixture of geopolymer engineering materials after hardening.

[0011] Preferably, the additive comprises the following components in parts by weight: 5-10 parts of cement, 1-4 parts of alkaline activator, 1-4 parts of early strength agent, 1-4 parts of gelling agent, and 1-4 parts of accelerating setting agent.

[0012] By adopting the above technical solution, the present application adds additives composed of cement, alkaline activator, early strength agent, gelling agent and accelerating setting agent on the basis of solid waste, which helps to improve the strength performance of geopolymer engineering materials.

[0013] Preferably, the cement is ferroaluminate cement or silicate cement.

[0014] By adopting the above technical solution, compared with silicate cement, the content of iron phase minerals such as tetracalcium aluminoferrate in ferroaluminate cement is higher, and the hydrated calcium ferrite produced after the hydration of iron phase minerals such as tetracalcium aluminoferrate is in a gel state, which helps to increase the total amount of gel produced after the geopolymer engineering material is mixed with water, and improves the filling effect of pores. At the same time, the hydrated calcium aluminate produced after the hydration of tetracalcium aluminoferrate can also combine with chloride ions to form hydrated calcium chloroaluminate (Friedel salt) with an effect of increasing strength. Therefore, after the use of ferroaluminate cement, the mechanical properties of the mixture of geopolymer engineering materials after hardening can be better improved.

[0015] Preferably, the components of the geopolymer engineering material also include tetracalcium aluminoferrite.

[0016] By adopting the above technical solution, due to the limitations of cement raw materials and firing process, there is an upper limit to the content of tetracalcium aluminoferrate in cement. By adding tetracalcium aluminoferrate single ore, the total amount of tetracalcium aluminoferrate in geopolymer engineering materials can be more effectively increased, thereby promoting the formation of gel products and hydrated calcium chloroaluminate, which helps to improve the mechanical properties of geopolymer engineering materials after hardening.

[0017] Preferably, the accelerating setting agent is an alumina clinker accelerating setting agent.

[0018] By adopting the above technical scheme, the alumina clinker accelerating setting agent can produce calcium aluminate hydrate while playing the accelerating setting role, which helps to increase the production of calcium chloroaluminate hydrate, not only improves the curing effect on chloride ions, but also can more fully improve the mechanical properties of geopolymer engineering materials after hardening.

[0019] Preferably, the gelling aid is lithium silicate.

[0020] By adopting the above technical solution, the permeability of lithium silicate is good, and lithium silicate can react with calcium ions in the reaction system under alkaline conditions to form calcium silicate gel, which helps to increase the total amount of gel produced after the geopolymer engineering material is mixed with water, improves the filling effect of the pores, and improves the mechanical properties of the geopolymer engineering material mixture after hardening.

[0021] Preferably, the alkaline activator is quicklime or carbide slag.

[0022] By adopting the above technical scheme, carbide slag is a solid waste produced by the carbide industry, and its main component is calcium hydroxide, and the product after quicklime hydration is also calcium hydroxide, so both carbide slag and quicklime can be used as alkaline activators, and in the scheme of the present application, the total amount of calcium hydroxide produced after the geopolymer engineering material is mixed with water can be adjusted. Compared with quicklime, carbide slag does not need to be ground before use because it has been digested, and the utilization cost is low. Although quicklime has a relatively high cost, the expansion effect of quicklime can improve the filling effect of pores, which helps to more fully improve the mechanical properties of the geopolymer engineering material after hardening.

[0023] Preferably, the early strength agent is ferric nitrate.

[0024] By adopting the above technical solution, iron nitrate reacts with calcium hydroxide produced by mixing geopolymer engineering materials with water to produce iron hydroxide gel and calcium nitrate. The iron hydroxide gel has a filling effect on pores and can play a densifying effect, which helps to improve the mechanical properties of the geopolymer engineering material mixture after hardening.

[0025] In a second aspect, the present application provides a construction method for solid waste-based geopolymer engineering materials for alkali residue treatment and comprehensive utilization, which adopts the following technical solution.

[0026] A construction method for solid waste-based geopolymer engineering materials for alkali residue treatment and comprehensive utilization comprises the following steps:

[0027] (1) preparing any of the above-mentioned solid waste-based geopolymer engineering materials for alkali residue treatment and comprehensive utilization for standby use;

[0028] (2) mixing the solid waste-based geopolymer engineering material for alkali residue treatment and comprehensive utilization with water, and stirring to obtain a geopolymer mixture;

[0029] (3) The construction is completed by spreading and compacting the geopolymer mixture in layers.

[0030] By adopting the above technical solution, the present application uses solid waste-based geological polymer engineering materials as engineering soil. After adding water and mixing to obtain the mixture, it is spread and compacted in layers to complete the construction process.

[0031] In summary, this application has the following beneficial effects:

[0032] 1. This application adds fly ash, iron tailings and desulfurized gypsum to the alkali slag, expands the types of solid waste used, and obtains solid waste-based geopolymer engineering materials. When the mixture formed by adding water to the geopolymer engineering material of this application is used as engineering soil for road base and yard cushion, it not only shows good compaction performance, but also has strong cementation between particles, which can better meet the mechanical performance indicators of engineering soil.

[0033] 2. In this application, the specific type of cement preferred is ferroaluminate cement or silicate cement. Ferroaluminate cement is more helpful to increase the total amount of gel products produced after the geopolymer engineering material is mixed with water, improving the filling effect of pores. At the same time, ferroaluminate cement produces more hydrated calcium aluminate after hydration, thus promoting the formation of hydrated calcium chloroaluminate. After selecting ferroaluminate cement, the mechanical properties of the mixture of geopolymer engineering materials after hardening can be better improved. DETAILED DESCRIPTION

[0034] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0035] Preparation example of additives

[0036] The following is an explanation using Preparation Example 1.

[0037] Preparation Example 1

[0038] In this preparation example, the additives include the following components: 5 kg of cement, 1 kg of alkaline activator, 1 kg of early strength agent, 1 kg of gelling agent, and 1 kg of accelerating setting agent. The cement is P.O42.5 silicate cement; the alkaline activator is carbide slag with an average particle size of 30 μm, the early strength agent is triethanolamine, the gelling agent is sodium silicate, and the accelerating setting agent is polymethacrylic acid (average molecular weight 35,000).

[0039] As shown in Table 1, the difference between Preparation Examples 1-5 is that the raw material ratios of the additives are different.

[0040] Table 1 Raw material ratio of additives

[0041]

[0042] Preparation Example 6

[0043] The difference between this preparation example and preparation example 3 is that the cement is ferroaluminate cement with a strength grade of 42.5.

[0044] Preparation Example 7

[0045] The difference between this preparation example and preparation example 6 is that the accelerating agent is an alumina clinker accelerating agent, the specific model is -N(Ⅲ) powder accelerating setting agent.

[0046] Preparation Example 8

[0047] The difference between this preparation example and preparation example 7 is that the gelling aid is lithium silicate.

[0048] Preparation Example 9

[0049] The difference between this preparation example and preparation example 8 is that the alkaline activator is ground quicklime (average particle size 30 μm).

[0050] Preparation Example 10

[0051] The difference between this preparation example and preparation example 9 is that the early strength agent is ferric nitrate.

[0052] Example

[0053] Examples 1-5

[0054] The following description is given by taking Example 1 as an example.

[0055] Example 1

[0056] This embodiment provides a solid waste-based geopolymer engineering material for alkali slag treatment and comprehensive utilization, including the following components in parts by weight: 56 kg of alkali slag, 18 kg of fly ash, 30 kg of iron tailings, 10 kg of desulfurized gypsum, and 1 kg of additives. The free calcium oxide content of the fly ash is 1%, and the additive is the additive of Preparation Example 1.

[0057] This embodiment also provides a construction method of solid waste-based geopolymer engineering materials for alkali residue treatment and comprehensive utilization, comprising the following steps:

[0058] (1) Prepare solid waste-based geopolymer engineering materials for alkali residue treatment and comprehensive utilization, and keep them ready for use;

[0059] (2) mixing the solid waste-based geopolymer engineering material for alkali residue treatment and comprehensive utilization with water at a water-solid ratio of 0.5, and obtaining a geopolymer mixture after stirring;

[0060] (3) The construction is completed by spreading and compacting the geopolymer mixture in layers.

[0061] As shown in Table 1, the differences between Examples 1-5 mainly lie in the different raw material ratios of solid waste-based geopolymer engineering materials and the free calcium oxide content of fly ash.

[0062] Table 1 Raw material ratio and free calcium oxide content of fly ash of solid waste-based geopolymer engineering materials

[0063]

[0064] Embodiment 6-9

[0065] As shown in Table 2, the difference between Examples 6-14 and Example 5 is that the preparation examples of the additives are different.

[0066] Table 2 Preparation examples of additives

[0067] sample Preparation Example sample Preparation Example Example 5 Preparation Example 1 Example 10 Preparation Example 6 Example 6 Preparation Example 2 Embodiment 11 Preparation Example 7 Example 7 Preparation Example 3 Example 12 Preparation Example 8 Example 8 Preparation Example 4 Example 13 Preparation Example 9 Example 9 Preparation Example 5 Embodiment 14 Preparation Example 10

[0068] Embodiment 15

[0069] The difference between this embodiment and embodiment 10 is that the components of the geopolymer engineering material also include tetracalcium aluminoferrite, and the amount of tetracalcium aluminoferrite is 30% of the weight of the cement.

[0070] Comparative Example

[0071] Comparative Example 1

[0072] The difference between this comparative example and Example 1 is that the solid waste-based geopolymer engineering material is replaced with alkali slag, and the alkali slag is mixed with water at a water-to-solid ratio of 0.5 and then cured until the specified age.

[0073] Comparative Example 2

[0074] The difference between this comparative example and Example 1 is that the components of the solid waste-based geopolymer engineering material do not include fly ash.

[0075] Comparative Example 3

[0076] The difference between this comparative example and Example 1 is that the components of the solid waste-based geopolymer engineering material do not include desulfurized gypsum.

[0077] Comparative Example 4

[0078] The difference between this comparative example and Example 1 is that the components of the solid waste-based geopolymer engineering material do not include iron tailings.

[0079] Performance testing methods

[0080] The mixture obtained in each embodiment and comparative example was placed in a test mold of 100mm×100mm×100mm, and then left to stand at room temperature, and demoulded after initial setting to obtain a test block. The test block was placed in a curing room with a humidity of 95% and a temperature of 20°C for curing. At the age of 28 days, an unconfined compression test was carried out using a TAW2000 press, and the loading speed during the test was 1mm / min.

[0081] The ratio of the unconfined compressive strength measured in each embodiment and comparative example to the unconfined compressive strength measured in comparative example 1 was calculated, and the ratio was recorded as relative strength. The results are shown in Table 3.

[0082] Table 3 Calculation results of relative strength

[0083]

[0084] Combining Examples 1-5 and Comparative Example 1 and Table 3, it can be seen that the relative strengths measured in Examples 1-5 are greater than those in Comparative Example 1, indicating that when the geopolymer engineering material of the present application is mixed with water to form a mixture, the fly ash undergoes a volcanic ash reaction to produce a certain amount of gel product. The gel product blocks part of the pores caused by the loss of salts and improves the cementation between the solid waste particles. At the same time, the iron tailings reduce the proportion of soluble salts in the geopolymer engineering material and play a certain filling role.

[0085] Combining Example 1 and Comparative Example 2 with Table 3, it can be seen that the relative strength measured in Example 1 is greater than that in Comparative Example 2, indicating that when there is a lack of fly ash in the geopolymer engineering material, it is difficult to form sufficient gel product after the geopolymer engineering material is mixed with water, and it is difficult to fully fill the pores generated by the loss of salts.

[0086] Combining Example 1 and Comparative Example 3 and Table 3, it can be seen that the relative strength measured in Example 1 is greater than that in Comparative Example 3, indicating that when desulfurized gypsum is lacking in the geopolymer engineering material, the excitation effect of the components in the alkali slag alone is limited, which is not conducive to fully meeting the mechanical properties of the engineering soil.

[0087] Combining Example 1 and Comparative Example 4 and Table 3, it can be seen that the relative strength measured in Example 1 is greater than that in Comparative Example 4, indicating that when there is a lack of iron tailings in the geopolymer engineering material, the proportion of soluble salts in the geopolymer engineering material is high, and the pores are difficult to be fully filled, which is not conducive to fully meeting the mechanical properties of the engineering soil.

[0088] It can be seen from Examples 5-9 and Table 3 that the use of the additives of Preparation Example 3 is more helpful in improving the strength of the test block, which is conducive to fully meeting the mechanical performance indicators of engineering soil.

[0089] Combining Example 7 and Example 10 with Table 3, it can be seen that the relative strength measured in Example 10 is greater than that in Example 7, indicating that due to the high content of iron phase mineral phases such as tetracalcium aluminate in ferroaluminate cement, the mechanical properties of the mixture of geopolymer engineering materials after hardening can be better improved after the ferroaluminate cement is selected.

[0090] Combining Example 10, Example 11 and Table 3, it can be seen that the relative strength measured in Example 11 is greater than that in Example 10, indicating that the alumina clinker accelerating setting agent can produce calcium aluminate hydrate while playing a quick-setting role, which helps to increase the amount of calcium chloroaluminate hydrate generated, not only improves the curing effect on chloride ions, but also can more fully improve the mechanical properties of the geopolymer engineering material after hardening.

[0091] Combining Example 11, Example 12 and Table 3, it can be seen that the relative strength measured in Example 12 is greater than that in Example 11, indicating that the permeability of lithium silicate is better, and calcium silicate gel can be more fully produced in the mixture, which helps to increase the total amount of gel produced after the geopolymer engineering material is mixed with water, improves the filling effect of the pores, and enhances the mechanical properties of the mixture of the geopolymer engineering material after hardening.

[0092] Combining Example 12, Example 13 and Table 3, it can be seen that the relative strength measured in Example 13 is greater than that in Example 12, indicating that the expansion effect of quicklime can improve the filling effect of pores, which helps to more fully improve the mechanical properties of geopolymer engineering materials after hardening.

[0093] Combining Example 13, Example 14 and Table 3, it can be seen that the relative strength measured in Example 14 is greater than that in Example 13, indicating that after the reaction between ferric nitrate and calcium hydroxide produced after the geopolymer engineering material is mixed with water, ferric hydroxide gel and calcium nitrate can be produced. The ferric hydroxide gel has a filling effect on the pores, can play a densifying effect, and is helpful to improve the mechanical properties of the mixture of the geopolymer engineering material after hardening.

[0094] Combining Example 15, Example 14 and Table 3, it can be seen that the relative strength measured in Example 15 is greater than that in Example 14, indicating that by adding tetracalcium aluminoferrate monoore, the total amount of tetracalcium aluminoferrate in the geopolymer engineering material can be more effectively increased, thereby promoting the formation of gel products and hydrated calcium chloroaluminate, which is helpful to improve the mechanical properties of the geopolymer engineering material after hardening.

[0095] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A solid waste-based geopolymer engineering material for alkali residue treatment and comprehensive utilization, characterized in that: The geopolymer engineering material comprises the following components in parts by weight: 56-64 parts of alkali slag, 18-22 parts of fly ash, 30-50 parts of iron tailings, 10-15 parts of desulfurized gypsum, and 1-5 parts of additives, wherein the additives include cement, alkaline activator, early strength agent, gelling agent and accelerating setting agent; The additive comprises the following components in parts by weight: 5-10 parts of cement, 1-4 parts of alkaline activator, 1-4 parts of early strength agent, 1-4 parts of gelling agent, and 1-4 parts of accelerating setting agent; The accelerating setting agent is an alumina clinker accelerating setting agent; The gelling aid is lithium silicate; The alkaline activator is quicklime or carbide slag; The early strength agent is ferric nitrate.

2. The solid waste-based geopolymer engineering material for alkali residue treatment and comprehensive utilization according to claim 1, characterized in that: The free calcium oxide content of the fly ash is 1-4%.

3. The solid waste-based geopolymer engineering material for alkali residue treatment and comprehensive utilization according to claim 1, characterized in that: The cement is selected from ferroaluminate cement or silicate cement.

4. The solid waste-based geopolymer engineering material for alkali residue treatment and comprehensive utilization according to claim 3 is characterized in that: The components of the geopolymer engineering material also include tetracalcium aluminoferrite.

5. A construction method for solid waste-based geopolymer engineering materials for alkali residue treatment and comprehensive utilization, characterized in that: The following steps are involved: (1) preparing any of the above-mentioned solid waste-based geopolymer engineering materials for alkali residue treatment and comprehensive utilization for standby use; (2) mixing the solid waste-based geopolymer engineering material for alkali residue treatment and comprehensive utilization with water, and stirring to obtain a geopolymer mixture; (3) The construction is completed by spreading and compacting the geopolymer mixture in layers.

Citation Information

Patent Citations

  • Chloride ion curing agent for ammonia-alkali process alkali residues as well as preparation method and application of chloride ion curing agent

    CN114804794A

  • In-situ tough well cementation cement, well cementation cement slurry and preparation method of well cementation cement slurry

    CN116262654A